The impact of student satisfaction and sense of belongingness on academic success and performance in undergraduate science majors - Kenney, Taziah; O'Halloran, Kim C. (Journal of Interdisciplinary Studies in Education, 2024)
Undergraduate students within science majors in the United States have more barriers than their peers, leading to lower rates of first-year retention and academic performance. To eradicate these barriers, research has sought to understand what factors influence retention and performance of science majors. Upon investigation, it was determined that undergraduate science majors’ levels of satisfaction with their institution and sense of belonging can impact their academic success and performance. Although dynamics influencing academic performance in science, technology, engineering, and mathematics (STEM) majors have been widely studied, very little research has sought to determine how a science major’s level of satisfaction with their institution and sense of belonging impact their academic success and performance. To investigate this, archival data including Student Satisfaction Inventory (SSI) information from science majors at a metropolitan private university in the Middle-Atlantic region of the United States were analyzed to determine how student satisfaction and sense of belonging impact academic success and performance.